Transgression and Transcendence - Gutowski, Piotr (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The text contains an analysis of the complex relationships between the two words: transcendence and transgression. They have a common core: “crossing or surpassing previous boarders or limits” and parts with different meaning. The most important opposition concerns surpassing human boundaries towards the divine ideal, and within traditional social order (in the case of transcendence) and questioning both God and that social order (in the case of transgression). By emphasizing this difference, these terms have become emblems of two strongly opposite worldviews: extreme conservatism and extreme liberalism. I argue that for communication reasons it is better to focus on common meaning and that on the road to individual and social maturity, both acts of transcendence and of transgression are necessary.